Microbial contamination of two non-sterile latex examination glove brands marketed in Trujillo, Peru: a laboratory study - Manuel Ángel García-Polo (TUMI Oral Health, 2026)
Introduction: Non-sterile latex examination gloves are routinely used as barrier protection in dental practice; however, microbial contamination may be present before clinical use and potentially compromise infection-control procedures. Objective: To compare the microbial contamination of two brands of non-sterile latex examination gloves marketed in Trujillo, Peru. Methods: A comparative laboratory study was conducted using 132 unused latex examination gloves, including 66 Endoglove and 66 BeeSure specimens. Gloves were aseptically removed from their original boxes and processed individually using a microbiological rinse procedure followed by incubation and culture. Microbial growth was quantified as colony-forming units (CFU), and recovered microorganisms were classified according to the laboratory identification. Results: Endoglove specimens yielded 95 CFU and BeeSure specimens 80 CFU. Overall, Klebsiella was the most frequently recovered bacterium (47 CFU; 26.86%), followed by Salmonella (38 CFU; 21.71%), enterococci (25 CFU; 14.29%), Staphylococcus epidermidis (21 CFU; 12.00%), yeasts (17 CFU; 9.71%), Staphylococcus aureus (14 CFU; 8.00%), and Staphylococcus saprophyticus (13 CFU; 7.43%). Conclusions: Microbial contamination was detected in unused non-sterile latex examination gloves from both brands, with a higher total CFU count in Endoglove than in BeeSure. Bacterial species predominated among the recovered microorganisms, particularly Klebsiella and Salmonella.